Awareness regarding organ transplantation among visitors of the ICU patients in three tertiary care centres in Kathmandu, a cross-sectional study - Shrestha, Gentle S.; Bhattarai, Amit S; Yonjen, Tseten; Bhandari, Ramesh S; Lakhey, Paleswan J; Acharya, Subhash P; Singh, Shreejana; Marhatta, Moda N (Journal of Advances in Internal Medicine, 2021)
Background and aims: Organ transplant is often the only viable treatment option for various end stage organ failures. Inadequacy of organ procurement from living as well as cadaveric donors is common, more so in developing countries. The aim of this study was to find out the knowledge and attitude regarding organ transplantation. Methods: A questionnaire-based survey was carried out among 150 respondents, who were the visitors of patients admitted to ICU of three tertiary care centres in Kathmandu. Results: Majority of the respondents were male 105 (70%) and 132 (88%) were aware about organ transplant. Likewise, 111 respondents (84.1%) hold the belief that organ transplant save lives. Ninety-four of the responses (34.8%) believe that media was the source of knowledge and 121 (91.7 %) of the respondents stated that organ transplant should be promoted. Majority of them, 80 of the total respondents (60.6%) believed that organ can be donated by both living and deceased donors and 111 (84.1%) of them believed that organ transplant save lives. While 88 of the respondents (66.7%) have heard about brain death, 60 of them (45.4%) believe that there is an organ transplant act in Nepal. Out of all respondents who are aware about transplantation, 91 of them (68.9%) have opinion that they are willing to donate the organ of their beloved ones should there be a situation of brain death. Conclusions: The study concludes that respondents have adequate knowledge regarding organ transplantation. Respondents have overall positive attitude towards organ donation and transplantation.